Gender-smart agriculture: An agenda for gender and socially inclusive climate-resilient agriculture - Huyer, Sophia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The working paper reviews the evolution of the CCAFS gender and social inclusion agenda towards gender equality and empowerment in relation to climate resilient agriculture. Climate change research typically shows glaring gaps in understanding the different adaptive strategies and capacities of men and women, and the technologies, practices, and enabling environments that will empower women. CCAFS approach to gender, therefore, has been to understand the gender gap in agriculture under climate change (CCAFS Phase I) while also researching climate-smart solutions to promote gender equality and women’s empowerment (CCAFS Phase II). A decade of gender research in CCAFS has led to the generation of a ‘Gender-Smart Agriculture’ approach. Gender research in CCAFS Phase I attempted to explore men’s and women’s adaptation options and strategies (individual, household, or collective) and the differences in their capacity to adapt. Data collected through household and intra-household surveys across CCAFS Climate Smart Village sites, highlighted influential findings on gender and CSA research by CCAFS and partners to date. The CCAFS work in Phase II (2017-2021) on Gender and Social Inclusion (GSI) expanded on this research to develop an approach, strategies, and monitoring frameworks for a gender-responsive, or gender-smart CSA. CCAFS targeted research to inform, catalyse and target CSA solutions to women and other vulnerable groups, increase the control of disadvantaged groups over productive assets and resources (e.g., climate information, climate finance), and increase participation in decision-making (e.g., in local and national climate adaptation strategies). GSI has also provided technical and funding support on gender and youth to policy analyses, inputs, and submissions (including NDCs and national climate policy), as well as capacity development to policy makers on gender in global and national climate policy. In addition, keeping in mind the importance of equipping practitioners and policy makers with tools and knowledge of innovative gender-transformative practices and intervention approaches, CCAFS has worked with partners to develop guidelines and toolkits for supporting this work.